Knightian uncertainty and stock-price movements: Why the REH present-value model failed empirically - Roman Frydman; Michael D. Goldberg; Nicholas Mangee (Kiel Institute for the World Economy (IfW), 2015)
Macroeconomic models that are based on either the rational expectations hypothesis (REH) or behavioral considerations share a core premise: all future market outcomes can be characterized ex ante with a single overarching probability distribution. This paper assesses the empirical relevance of this premise using a novel data set. We find that Knightian uncertainty, which cannot be reduced to a probability distribution, underpins outcomes in the stock market. This finding reveals the full implications of Robert Shiller's ground-breaking rejection of the class of REH present-value models that rely on the consumption-based specification of the risk premium. The relevance of Knightian uncertainty is inconsistent with all REH models, regardless of how they specify the market's risk premium. Our evidence is also inconsistent with bubble accounts of REH models' empirical difficulties. We consider a present-value model based on a New Rational Expectations Hypothesis, which recognizes the relevance of Knightian uncertainty in driving outcomes in real-world markets. Our novel data is supportive of the model's implications that rational forecasting relies on both fundamental and psychological factors.
Keywords: E44; G12; 330; Knightian uncertainty; structural change; fundamentals; psychology; present-value model; stock prices